2015
DOI: 10.1515/cmble-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Is there a connection between inflammation, telomerase activity and the transcriptional status of telomerase reverse transcriptase in renal failure?

Abstract: Telomerase is involved in the elongation of telomeres. It remains active in very few types of cell in mature organisms. One such cell type is the lymphocytes. In this study, we investigated the activity and expression of telomerase in lymphocytes from renal failure patients and compared it to that for normal controls. Inflammation status was determined at the same time. The enzyme activity was measured using PCR-ELISA with peripheral blood mononuclear cells (PBMCs) from three groups: 53 healthy individuals, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…Moreover, this activity was lower in patients with intermediate stages of CKD and not in dialysis ones, though the enzyme’s activity was also found to be pathological in dialysis when compared to normal controls. In addition, hTERT exhibited low levels of expression in intermediate stages of the disease but not in dialysis patients while our study also confirmed the inflammatory status of these patients [ 130 , 131 ]. Similarly, it has been reported that telomere length is affected from CKD duration when measured in DNA from whole blood samples.…”
Section: The Telomere/telomerase System In Chronic Disorders Is Isupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, this activity was lower in patients with intermediate stages of CKD and not in dialysis ones, though the enzyme’s activity was also found to be pathological in dialysis when compared to normal controls. In addition, hTERT exhibited low levels of expression in intermediate stages of the disease but not in dialysis patients while our study also confirmed the inflammatory status of these patients [ 130 , 131 ]. Similarly, it has been reported that telomere length is affected from CKD duration when measured in DNA from whole blood samples.…”
Section: The Telomere/telomerase System In Chronic Disorders Is Isupporting
confidence: 81%
“…TNF-a, CRP, IL-6, IL-1, IL-23, reactive oxygen species (ROS) and others, have all been implicated in promoting impaired renal function [ 129 ]. Impaired immunity/inflammation can be predictors of mortality and morbidity contributing to the risk of CKD and it seems very likely that telomeres/telomerase are very important aspects of this relationship [ 130 , 131 ]. Oxidative stress and chronic inflammation can cause lymphocyte telomere shortening resulting in T-cell dysfunction and ultimately susceptibility to kidney infection and injury.…”
Section: The Telomere/telomerase System In Chronic Disorders Is Imentioning
confidence: 99%
“…7 In particular, it has been shown that chronic inflammation leads to lymphocyte telomere attrition, cell senescence, and finally impairment of the immune response. 8 This T-cell dysfunction can contribute to increased susceptibility to kidney infections and injury. 7 Chronic kidney disease (CKD) is a complex disease, and its heritability has been estimated to be 30%-70%.…”
mentioning
confidence: 99%
“…[ 48 ] Furthermore, chronic low-grade inflammation may also be related to intracellular telomere reduction. Kordinas et al [ 49 ] reported that the levels of inflammatory mediators, such as IL-6 and CRP, increased and telomerase activity decreased in patients with CKD. This decrease in telomerase activity accelerates telomere shortening, thus accelerating cell senescence, the basis of frailty and aging.…”
Section: Possible Pathogenesis Of Frailty In Kt Candidates and Recipi...mentioning
confidence: 99%